2014
DOI: 10.5535/arm.2014.38.5.682
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effect of Intrathecal Gabapentin in a Rat Model of Persistent Muscle Pain

Abstract: ObjectiveTo evaluate the analgesic effect of intrathecal gabapentin therapy on secondary hyperalgesia in a rat model of persistent muscle pain.MethodsIntrathecal catheters were implanted into rats. Mechanical secondary hyperalgesia was induced by repeated intramuscular injections of acidic solution into the gastrocnemius muscle. Gabapentin was administrated intrathecally. Rats were allocated to control and experimental (gabapentin 30, 100, 300, and 1,000 µg) group. After gabapentin administration, mechanical w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
1
3
0
2
Order By: Relevance
“…Through Western blot analysis, our data show that gabapentin significantly diminishes the membrane translocation of PKC and the phosphorylation levels of ERK1/2, suggesting that the analgesic effect of gabapentin is mediated through the suppression of PKC and ERK1/2 signaling pathways. In addition, numerous studies have identified gabapentin as a NMDA receptor blocker and a voltage-gated calcium channel blocker [ 6 8 ]. NMDA and calcium receptor activation in the peripheral and central nervous systems have been shown to be involved in the development and maintenance of various pain states, including neuropathic pain and visceral pain [ 14 , 15 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through Western blot analysis, our data show that gabapentin significantly diminishes the membrane translocation of PKC and the phosphorylation levels of ERK1/2, suggesting that the analgesic effect of gabapentin is mediated through the suppression of PKC and ERK1/2 signaling pathways. In addition, numerous studies have identified gabapentin as a NMDA receptor blocker and a voltage-gated calcium channel blocker [ 6 8 ]. NMDA and calcium receptor activation in the peripheral and central nervous systems have been shown to be involved in the development and maintenance of various pain states, including neuropathic pain and visceral pain [ 14 , 15 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, the USA Food and Drug Administration approved gabapentin, a γ-aminobutyric acid derivative, for clinical use in the treatment of neuropathic pain. Since then, gabapentin has been extensively applied in the field of analgesia [ 6 9 ]. Preliminary data from animal experiments have confirmed the analgesic effects of gabapentin on visceral pain, but the mechanism of this effects remains unknown [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Desta forma, o efeito antinociceptivo da gabapentina em modelo de dor muscular crônica induzida por CFA foi constatado. Estes resultados corroboram com um único estudo prévio de dor musculoesquelética tratada com gabapentina que demonstrou seu efeito analgésico em ratos com hiperalgesia mecânica após injeção de salina ácida no músculo gastrocnêmio (Kang et al, 2014).…”
Section: Discussionunclassified
“…Estudos têm demonstrado que a gabapentina pode inibir respostas dolorosas por meio de sua ligação à subunidade α2/δ-1 de canais de cálcio dependentes de voltagem presente em neurônios e redução de substâncias como glutamato, substância P, NF-kB e CGRP (Fink et al, 2000;Kukkar et al, 2013;Park et al, 2008;Quintero et al, 2011;Yaksh, 2006). Além disso, sabe-se que a gabapentina apenas prejudica funções motoras em doses elevadas (Kang et al, 2014).…”
Section: Discussionunclassified